Empowering Local Tailors with E-Catalog Creation and Digital Marketing: a Case Study from SMEs at Demak - Nahda, Katiya; Setyaning, Alldila Nadhira Ayu (Asian Journal of Community Services, 2024)
This program is designed to boost the digital prowess of tailors in the Semarang-Demak toll area, mentored by PT PPSD. Focused on e-catalog creation and digital marketing, it aims to sharpen their online marketing and cataloging skills. The goal is to widen their market presence, increase sales, and adapt to evolving digital trends. The initiative includes foundational training in e-catalog tools and digital marketing tactics, along with practical social media promotion strategies. Interactive workshops and mentorship sessions further reinforce this learning. By fostering collaboration between PT PPSD, the tailors, and our support team, we are not just driving immediate sales growth; we are equipping these artisans with enduring skills to thrive in today's competitive marketplace.